2013
DOI: 10.1016/j.jmmm.2012.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall effect in perpendicularly magnetized thin films

Abstract: Mn3−xGa (x = 0.1, 0.4, 0.7) thin films on MgO and SrTiO3 substrates were investigated with magnetic anisotropy perpendicular to the film plane. An anomalous Hall-effect was observed for the tetragonal distorted lattice in the crystallographic D022 phase. The Hall resistivity xy was measured in a temperature range from 20 to 330 K. The determined skew scattering and side jump coefficients are discussed with regard to the film composition and used substrate and compared to the crystallographic and magnetic prope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…For 30nm Mn 1.86 Ga it is a factor 2 higher as previously reported 7 . It is known that disorder in Mn 3−x Ga thin films affects the total magnetic moment 12 . M appears to be constant even within the strained range of thickness, therefore no significant site disorder is occuring with the decreasing film thickness.…”
Section: Fig 1 Range Of the Binary Mn-ga Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…For 30nm Mn 1.86 Ga it is a factor 2 higher as previously reported 7 . It is known that disorder in Mn 3−x Ga thin films affects the total magnetic moment 12 . M appears to be constant even within the strained range of thickness, therefore no significant site disorder is occuring with the decreasing film thickness.…”
Section: Fig 1 Range Of the Binary Mn-ga Compoundmentioning
confidence: 99%
“…However, the bulk vacancy distribution model is not entirely consistent with the thin film model 7 and the detailed mechanism is still unclarified. Many groups have been investigating varying composition ranges in bulk and thin films 7 ranging from Mn 1−x Ga x (x=0.6) 8 to Mn 3−x Ga (0≤x≤1) [9][10][11][12][13] . The reports about Mn-Ga however are mostly limited to a film thickness of 20-100nm and don't examine the effects of reducing the layer a) Electronic mail: albrecht.koehler@cpfs.mpg.de b) Electronic mail: Stuart.Parkin@us.ibm.com…”
mentioning
confidence: 99%
“…Tetragonal s-Mn 3 Ga has attracted much attention due to the wide variety of technological applications ranging from substitution of rare-earth permanent magnets 1-3 with nanostructured Mn 3Àx Ga to spintronics applications using epitaxial thin films. 4,5 This phase has the Al 3 Ti-type (D0 22 space group I4/mmm) crystal structure and exhibits a ferrimagnetic (FiM) coupling along c axis. 6 This FiM order is produced by the interatomic separation of two different Mn positions, namely, Mn I and Mn II atoms, which nearest neighbor atomic separation is 2.56 Å .…”
mentioning
confidence: 99%
“…Electrical transport properties were characterized in those¯lms, and high electrical resistivity and large anomalous Hall e®ect were found. 35 Subsequently, several groups have reported the structure and PMA of 38 and then discussed the origin, i.e., the skew scattering and side jump. Microscopic investigation on spin and orbital magnetic moments has been done recently using X-ray magnetic circular dichroism by Rode et al 39 Small orbital magnetic moment was suggested (less than 0:2 B ), even though it was, in principle, a source of magnetic anisotropy.…”
Section: Structure and Magnetic Properties Of Mn-ga Filmsmentioning
confidence: 99%